Cell death induced by eluates from hypoallergenic denture base acrylic resins in NIH-3T3 fibroblast cells - Gulay Kansu; Tugba Kalyoncuoğlu; Pembegul Uyar; Esra Uzun (Elsevier, 2014)
Background/purpose: The use of a hypoallergenic denture base material for dental patients is susceptible to trigger allergic reactions. The aim of this study was to compare the cytotoxicity at the cellular level of hypoallergenic denture base materials and polymethyl methacrylate denture base materials polymerized in different ways. Materials and methods: Comparisons were done with the MTT (3-4,5-dimethylthiazol-2-yl)-2,5-dephenyltetrazolium bromide) results of eluates, which were derived from all test materials by immersing for 24 and 48 hours in various ratios of the test materials' weights to the volume of Dulbecco's modified Eagle's medium without supplements (0.2, 0.4, and 0.8 g/mL) and incubating NIH-3T3 cells for 24 and 48 hours (N = 9). Then the apoptotic effects of the materials were detected, using the TUNEL (terminal deoxynucleotidyl transferase dUTP nick end labeling) assay. Results: The 24-hour eluates of all materials exhibited strong cytotoxicity, and cytotoxicity increased with time but the difference was not statistically significant. In terms of cell death rates, the materials were ranked as follows: QC 20, Puran HC, Acron MC, Promysan Star. As a result of the apoptotic index of the materials, the ratio of necrotic cells was found from highest to lowest: QC 20, Puran HC, Acron MC, and Promysan Star. Conclusion: It was determined that the test materials have cytotoxic effects on fibroblasts, and polymethyl methacrylate-based test materials have a more necrotic effect on cells; however, other test materials induced apoptosis at a higher range.